The Evaluation of Disasters - Michael Scriven (Journal of MultiDisciplinary Evaluation, 2005)
In the last few years, we have seen some mighty catastrophes on the face of the earth, some wrought by human hands directly and others from great national disasters. We must ask, what has evaluation contributed to aiding humankind cope with these events, and what could it contribute that it has not so far provided?